P4-S3.07 Population genomics of Trichomonas vaginalis reveals a globally distributed two-phylotype population structure. (10th July 2011) - Conrad, M; Gorman, A; Schilinger, J; Sullivan, S; Upcroft, J; Gonzalez, J; Fiori, P L; Arroyo, R; Ravel, J; Secor, W E; Carlton, J
Abstract : Objective: Trichomonas vaginalis, the causative agent of human trichomoniasis, is the most prevalent non-viral sexually transmitted infection and has been associated with increased risk of HIV transmission, making detection and treatment a global health priority. In this study, we evaluate the population genomics of globally distributed clinical isolates to characterise genetic diversity and identify population structure. Methods: We use a panel of 21 microsatellite and three single copy gene markers to evaluate the population genomics of 18 clinical isolates collected from female patients attending New York City STD clinics in 2008, as well as 177 extant isolates collected from the USA, Mexico, Chile, Italy, Southern Africa, Papua New Guinea, and Australia. We use a panel of population genetic tools including Arlequin 3.11 and FSTAT to calculate expected heterozygosity (HE) and population differentiation (FST) statistics. To infer population structure, we use STRUCTURE 2.2, Network 4.516, and SeaView 4.2.4. We test for significance in clinical and demographic variables (χ 2 and t-tests) using JMP Genomics 5.0. Results: We detect significant genetic diversity within the species (HE=0.66) that is observed across global regions (range 0.52–0.67), and find that a two-phylotype population structure is maintained globally with few instances in population differentiation defined by geographical origin. This two-phylotype structure is further supported by minimum spanning networks, hierarchical clustering and phylogenies inferred from three single copy genes. These two phylotypes appear at nearly equal frequencies globally. Defining characteristics of the phylotypes include significantly different prevalence of T vaginalis virus infection (3% in phylotype 1 and 73% of phylotype 2 (p<0.0001, χ 2 )) see Abstract P4-S3.07 figure 1 and a significantly higher minimum inhibitory concentration of metronidazole in phylotype 1 (p=0.0024, χ 2 Wilcoxon Rank Sums). Conclusions: We detect clear population structure and high levels of genetic diversity from global T vaginalis isolates. This preliminary data suggests that phylotypes differ phenotypically. An accurate survey of genetic diversity and population structure will facilitate responsible selection of drug and/or vaccine targets for future treatments, and will enable better understanding of virulence factors contributing to the wide range of severity of symptoms associated with trichomoniasis.